Motivators and impediments to seismic retrofit implementation for wood-frame soft-story buildings: A case study in California. Issue 4 (November 2022) - Zhang, Yating; Fung, Juan F; Johnson, Katherine J; Sattar, Siamak
Motivating property owners to mitigate seismic risks for existing buildings is a major challenge for many earthquake-prone regions. This article identifies primary factors that may affect the adoption of seismic retrofit by owners of commercial and residential buildings, assesses the influence of economic, social, regulatory, and individual factors on retrofit implementation in three California cities, and discusses potential approaches to promoting seismic retrofits. Data for three retrofit programs are utilized to create predictive models for retrofit probability. The results suggest that retrofit probability for multifamily residential buildings may increase with building height, median housing value, educational attainment, and population density in the neighborhood, but may decrease with building age, building size, land value, and housing vacancy rate in the neighborhood. The retrofit decision for commercial buildings is strongly correlated with the number of stories and rooms, land value, vacancy rate, and population density, while the retrofit decision for residential buildings is highly associated with building age, number of rooms, land value, median housing value, median contract rent, and educational attainment. Overall, promoting seismic retrofits requires careful consideration of different motivators and impediments to owner's retrofit actions for commercial and residential buildings, and for older, taller, larger buildings, which tend to be more vulnerable but are associated with higher retrofit costs. In addition, neighborhood characteristics including median housing value and vacancy rate may be strong indicators of the retrofit probability among building clusters.